Polycystic ovary syndrome - 80 years of research and new directions in the study (literature review) - L. V. Damdinova; O. Ya. Leshchenko (Acta Biomedica Scientifica)
The article presents the current data of history of polycystic ovary syndrome (PCOS) study. It contains studies of genetic susceptibility of PCOS, PCOS symptoms and connection with development of anxiety and depressive disorders. The article covers ethnic differences in the phenotypic manifestations of PCOS. The papers describes the study of endocrine causes of infertility in Russian and Buryat women. Several theories of PCOS, including the theory of PCOS connection with intestinal bacterial flora disorders ("dysbiotic intestinal microbiota") are being discussed. The article also provides an overview of various scientific research in this area and the data of the relationship of PCOS and the risk of cardiometabolic disorders, insulin resistance, metabolic syndrome, obesity and sleep apnea. It highlights modern aspects in the study of PCOS etiology - studies of adipose tissue as an endocrine organ. The article reflects study of PCOS relationship with the level of the gastrointestinal tract hormones: leptin, insulin, ghrelin, cholecystokinin, peptide YY. The effect of short-term low-dose hormonal contraceptives on appetite levels in PCOS is covered. The scientific articles on the severity of hypertension in menopausal women with PCOS history and the presence of overweight are reviewed. The scientific work determines molecular genetic markers of PCOS in the aspect of the influence of environmental factors on the expression of genes.